Nomographic A system for calculating water requirements - Whittembury, Guillermo (1956)
Urine volume, total urinary osmolality and urinary osmolar concentration: A nomographic system that relates these variables. The insensible loss was taken as a constant, with a value of 0.42 cm3 / Cal / 24 hours. The nomographic system calculates the total requirement and urinary water in cm3 / 24 hours, cm3 / kg. weight / 24 hours in cm3 / Cal / 24 hours. The authors discuss the practical applications of this system and its limitations nomographic.